Racemic [alpha]-cyclohexyl-mandelic acid resolution across hollow fiber supported liquid membrane - Huang, D. (Array, 2008)
Summary: This paper deals with the resolution of racemic -cyclohexyl-mandelic acid containing copper(II) N-dodecyl-(L)-hydroxyproline (CuN2) as a chiral carrier across hollow fiber supported liquid membrane. A mathematical model of transport and resolution of chiral compounds was deduced, the observed partition coefficient between the feed phase and the membrane phase, the stripping phase and the membrane phase, mass transfer resistance of boundary layer in strip phase inside the hollow fibers, boundary layer in feed phase and mass transfer resistance of the membrane phase are taken into account in the model equations. Using the experimental results, several parameters of the proposed model have been achieved by a nonlinear fitting method. It is a simply mathematical model which can be easily used to predict the concentration of the enantiomers and the separation factor of the resolution process